Hubungan Riwayat Trauma Terhadap Kejadian Abortus Di Rsud Ulin Banjarmasin Tahun 2011 - Aditya Noor Rachman; Hardyan Sauqi; Nelly Al Audhah (Berkala Kedokteran, 2013)
ABSTRACT: The word abortion derives from the Latin aboriri, which means miscarry. Abortion is a controversial issue because on one side of abortion exist in society.Of the 210 million pregnancies that occur each year, about 46 million (22 %) end in induced abortion and, globally, the vast majority of women are likely to have at least one abortion by the time they are 45 years old. The most common causes of trauma during pregnancy are motor vehicle accidents (49%), falls (25%), assaults (18%), guns (4%), and burns (1%). This research aims to determine and analyze the relationship between history of trauma with abortion incident. This is an analytic descriptive research with cross sectional approach. The number of samples obtained from medical records at RSUD Ulin Banjarmasin in 2011. Achieved total sample of 251 people and the amount of control as much as 323 people. Samples that have a history of trauma were 41 (16%) people, and without a history of trauma as much as 210 (84%). The results of chi-square statistical test demonstrated an association between a history of trauma with the incidence of abortion in RSUD Ulin Banjarmasin, obtained probabilities of 0.000 means that the two variables are related because the score < 0.05. While the prevalence odds ratio (POR) through the test of the correlation coefficient obtained figure of 7,688 which means the power relationship is strong. In conclusion there is a significant relationship between history of trauma with the incidence abortion. Keywords: history of trauma, abortion, abdominal massage ABSTRAK: Abortus merupakan suatu masalah kontroversi karena di satu pihak abortus ada di masyarakat. Sekitar 210 juta kehamilan yang terjadi setiap tahun, sekitar 46 juta (22%) berakhir karena abortus. Salah satu penyebab abortus adalah trauma. Penyebab paling umum dari trauma selama kehamilan adalah kecelakaan kendaraan bermotor (49%), jatuh (25%), kekerasan (18%), senjata api  (4%), dan luka bakar (1%). Penelitian ini bertujuan untuk menganalisis hubungan antara riwayat trauma terhadap kejadian abortus pada ibu hamil di RSUD Ulin Banjarmasin 2011. Penelitian ini bersifat deskriptif analitik dengan pendekatan cross sectional. Sampel diperoleh dari rekammedis di Rumah Sakit Ulin Banjarmasin tahun 2011. Didapatkan jumlahsampel sebanyak 251 orang dan jumlah control sebanyak 323 orang. Sampel yang memiliki riwayat trauma sebanyak 41 (16%) orang, dan tanpa riwayat trauma sebanyak 210 (84%). Hasil uji statistic chi-square menunjukkan terdapat hubungan antara riwayat trauma dengan kejadian abortus di RSUD Ulin Banjarmasin, didapatkan angka  probabilitas sebesar  0,000 artinya kedua variable tersebut berhubungan karena angkanya < 0,05. Sedangkan prevalence odds ratio (POR) melalui uji koefisien korelasi didapatkan angkasebesar 7,688 yang berarti kekuatan hubungannya kuat. Kesimpulannya ada hubungan bermakna antara riwayat trauma dengan angka kejadian abortus. Kata-kata kunci: riwayat trauma, abortus, pijatperut